2020
DOI: 10.1016/j.gca.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Controls of extreme isotopic enrichment in modern microbialites and associated abiogenic carbonates

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…This dispersion is among the highest known in the Central Andes (Figure 9) and elsewhere (Figure S3). A greater dispersion of isotope values has only been observed at Laguna Negra in Argentina (17.3% in δ 13 C; 11.3% in δ 18 O) where the amplitude results not only from temporal variations in moisture, which are recorded in microbialites (temporal amplitude varying from 4% to 11% for δ 13 C, and 3% to 8% for δ 18 O) [9], but also from spatial controls driven by the diversity of depositional environments (inlet mixing with lake, or lake alone) [9,56]. Differences in depositional environments strongly affect the isotope record, even over short distances.…”
Section: Laguna Pastos Grandes In Comparison With Other Andean Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…This dispersion is among the highest known in the Central Andes (Figure 9) and elsewhere (Figure S3). A greater dispersion of isotope values has only been observed at Laguna Negra in Argentina (17.3% in δ 13 C; 11.3% in δ 18 O) where the amplitude results not only from temporal variations in moisture, which are recorded in microbialites (temporal amplitude varying from 4% to 11% for δ 13 C, and 3% to 8% for δ 18 O) [9], but also from spatial controls driven by the diversity of depositional environments (inlet mixing with lake, or lake alone) [9,56]. Differences in depositional environments strongly affect the isotope record, even over short distances.…”
Section: Laguna Pastos Grandes In Comparison With Other Andean Contextsmentioning
confidence: 99%
“…In the ephemeral central lake of Pastos Grandes, the slightly negative values (between −2.5% and −0.6% for δ 13 C; −3.4% and −1.5% for δ 18 O) were low compared to values for other Andean lacustrine carbonates (including mud and microbialites), particularly the values for δ 13 C. In fact, other Andean lakes frequently record higher values, with some almost reaching +10% for both δ 13 C and δ 18 O (e.g., Laguna Negra and El Peinado in Argentina, and Laguna Seca and Laguna del Negro Francisco in Chile; Figure 9). Even though some latitudinal variations in precipitation exist, which may induce some changes in the initial δ 18 O coming from rainfall, the strong evaporation ruling over the Central Andes affects the isotope record, inducing very positive δ 18 O values, (e.g., [56]), enhanced by the perennial character of the lakes with a relatively long water residence time [4,52,57]. In such lakes, partial evaporation favors the escape of light oxygen isotopes ( 16 O), so that heavy oxygen isotopes ( 18 O) accumulate in lake water over the years.…”
Section: Laguna Pastos Grandes In Comparison With Other Andean Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these settings, carbonate with δ 13 C values between -25 and +15‰ have been documented (Fig. 3), with rapid invasion of CO 2 leading to low δ 13 C carb values (Clark et al 1992) and degassing of CO 2 leading to high δ 13 C carb values (Beeler et al 2020). It is unclear if kinetic effects are expressed in stratigraphic δ 13 C carb records, but it has been suggested that these processes may have been more pronounced in Precambrian platform environments, where abiotic or microbially-mediated carbonate precipitation likely was more important (Ahm et al 2019;Husson et al 2020).…”
Section: Local Variability In Carbon Sources and Sinksmentioning
confidence: 95%
“…Surface waters that have low DIC concentrations with net CO 2 invasion may therefore have lower δ 13 C DIC values compared to surface waters with high DIC concentration and net CO 2 degassing (Wanninkhof 1985). The isotope effects of air-sea gas exchange can dampen the δ 13 C DIC enrichment from the biological pump in surface waters, but in the modern ocean these kinetic effects are relatively small, leading to spatial variability in surface waters δ 13 C DIC of the open ocean of up to 2‰ (Lynch-Stieglitz et al 1995) In contrast to the modern surface-ocean, kinetic isotope effects associated with CO 2 exchange can be pronounced in hypersaline and restricted environments (e.g., Lazar and Erez 1992;Clark et al 1992;Beeler et al 2020). In these settings, carbonate with δ 13 C values between -25 and +15‰ have been documented (Fig.…”
Section: Local Variability In Carbon Sources and Sinksmentioning
confidence: 99%